Preparation and photocatalytic activity of CuO/ZnO composite nanostructured films. (22nd October 2018) - Huang, Jin-Hua; Chen, Jia-Xing; Tu, Ya-Fang; Tian, Yu; Zhou, Di; Zheng, Guang; Sang, Jian-Ping; Fu, Qiu-Ming
Abstract: CuO/ZnO composite nanostructured films have been prepared by a simple two-step low-temperature hydrothermal approach. The morphology and structure characterizations demonstrated that CuO coral-like nanostructures were deposited on ZnO nanorod arrays. Experiment on the degradation of methylene blue under Xe lamp irradiation was carried out to evaluate the photocatalytic activities of the samples. It was found that the CuO/ZnO composite nanostructured films exhibited enhanced photocatalytic performances compared with the pure ZnO. This improvement can be ascribed to the enhanced visible light absorption and effective separation of photoexcited electrons and holes.